Literasi Matematika untuk Pembangunan Berkelanjutan Kerangka Kerja untuk Mengintegrasikan SDGs PBB dalam Pendidikan Matematika - Rista Faradila; Nursalam; Andi Kusumayanti (Pendidikan Matematika FKIP Universitas Mataram, 2025)
This study aims to analyze the integration of Mathematical Literacy and the Sustainable Development Goals (SDGs) in mathematics education using a Systematic Literature Review (SLR) approach. The emphasis is on how mathematics learning can support sustainable development by improving higher-order thinking skills. A total of 43 scientific articles published between 2020 and 2025 were collected from Scopus, ScienceDirect, SpringerLink, and Taylor & Francis Online, then analyzed thematically using content analysis. The SLR process followed the PRISMA protocol consisting of four steps: identification, screening, eligibility evaluation, and inclusion. Inclusion criteria included articles discussing the integration of SDGs or Education for Sustainable Development (ESD) in the context of mathematics education, indexed in Scopus, and in English. The results of the study show that there are five main themes: the role of teachers as key agents of transformation, mathematics curriculum: gaps and opportunities, the role of technology and digital innovation in the learning process, affective and well-being approaches to learning, and interdisciplinary collaboration for transformative learning. The integration of SDGs is currently still limited, but has great potential if supported by ESD-based teacher training, adaptive curriculum, and the use of innovative learning technology to build students' social and ecological awareness.